Introduction to the special issue “Parliamentary formations and diversities in (post-)imperial Eurasia” - Sablin, Ivan (Journal of Eurasian studies, 2020)
Addressing the entangled histories of deliberative decision making, political representation, and constitutionalism in several geographic and temporal contexts, this Special Issue offers nuanced political and intellectual histories and anthropologies of parliamentarism in Eurasia. It explores parliaments and quasi-parliamentary formations and the designs of such in the Qing and Russian Empires, the late Soviet Union, Ukraine, the Russian Far East, and the Russian-Mongolian borderlands (from Buryat and Mongolian perspectives) in seven contributions. Apart from the regional interconnections, the Special Issue foregrounds the concepts of diversity and empire to enable an interdisciplinary discussion. Understanding empires as composite spaces, where the ambivalent and situational difference is central for the governing repertoires, the articles discuss social (ethnic, religious, regional, etc.) diversity in particular contexts and the ways it affected the parliamentary designs. The multitude of the latter is understood as institutional diversity and is discussed in relation to different levels of administration, as well as the positions of respective parliamentary formations within political systems and their performance within regimes. The contributions also investigate different forms of deliberative decision-making, including the soviet, the Congress of People’s Deputies, and the national congress, which allows to include conceptual diversity of Eurasian parliamentarisms into the discussions in area and global studies. The Special Issue highlights the role of (quasi-)parliaments in dissembling and reassembling imperial formations and the ways in which parliaments were eclipsed by other institutions of power, both political and economic.